Religi Masyarakat Periferi: Analisis Rites of Passage Atas Ruwatan Rambut Gimbal di Dieng - Hamsah, Ustadi (FIKRAH, 2020)
This article aims to see the traditions associated with the existence of the Absolute which will give birth to a unique and distinctive ritual system in the ritual of ruwatan dreadlocks in Dieng. Perception of myths and cultural phenomena with a sublimated perspective and is an innovation for the central tradition in the Ngayogyokarto Hadiningrat Palace. There was a "movement" of the central culture that pulled over (periphery) and manifested itself into a "religious" ritual carried out by the community. The problem that arises is how the ritual tradition of ruwatan dreadlocks is interpreted as a religiosity that is not practiced in the palace, as well as what it means for the people of Dieng. Data were collected using participatory observation methods, in-depth interviews, document studies, and focus group discussions. The analysis uses techniques of deep analysis by applying the perspective rites of passage from Arnold van Gennep and Victor Turner. The result and analysis are that there is a positive compromise between the concept of holiness and more worldly concepts such as economic interests (tourism) which is a form of cultural reaggregation in Dieng. AbstractThis article aims to see the traditions associated with the existence of the Absolute which will give birth to a unique and distinctive ritual system in the ritual of ruwatan dreadlocks in Dieng. Perception of myths and cultural phenomena with a sublimated perspective and is an innovation for the central tradition in the Ngayogyokarto Hadiningrat Palace. There was a "movement" of the central culture that pulled over (periphery) and manifested itself into a "religious" ritual carried out by the community. The problem that arises is how the ritual tradition of ruwatan dreadlocks is interpreted as a religiosity that is not practiced in the palace, as well as what it means for the people of Dieng. Data were collected using participatory observation methods, in-depth interviews, document studies, and focus group discussions. The analysis uses techniques of deep analysis by applying the perspective rites of passage from Arnold van Gennep and Victor Turner. The result and analysis are that there is a positive compromise between the concept of holiness and more worldly concepts such as economic interests (tourism) which is a form of cultural reaggregation in Dieng.Keywords: Dieng, periphery, rambut gimbal (clump hair), rites of passage AbstrakArtikel ini bertujuan untuk melihat tradisi yang terkait dengan eksistensi Yang Maha Mutlak akan melahirkan sistem ritual yang unik dan khas pada ritual ruwatan rambut gimbal di Dieng, yang merupakan wilayah terpencil dan periferi dari tradisi dan budaya Jawa yang berpusat di Kraton Ngayogyokarto Hadiningrat. Mempersepsi mitos dan fenomena budaya dengan cara pandang yang mengalami sublimasi dan merupakan inovasi bagi tradisi pusat di kraton. Terjadi “gerak” budaya pusat yang menepi (periferi) dan termanifestasi menjadi sebuah ritual “religius” yang dilakukan oleh masyarakat. Persoalan yang muncul adalan bagaimana tradisi ritual ruwatan rambut gimbal dimaknai sebagai sebuah religiusitas yang tidak dilakukan di pusat tradisi (kraton), serta bagaimana makna bagi masyarakat Dieng. Dengan menggunakan perspektif rites of passage artikel berikut ini menguraikan fenomena tersebut. Hasil dan analisis adalah adanya kompromi positif antara konsep kesucian dengan konsep-konsep yang lebih duniawi seperti kepentingan ekonomi (pariwisata) yang merupakan bentuk reagregasi budaya di Dieng.Kata kunci: Dieng, periferi, rambut gimbal, ritus peralihan